Digital competence of English language teachers - Godárová, Vanessa (Univerzita Pardubice, 2024)
This diploma thesis deals with the digital competence of teachers in a basic school (primary and lower-secondary). In the theoretical part, the characteristics of a teacher are defined from a general point of view together with the competences of a teacher. Furthermore, the terms are put into the context of English language teaching and together, they are described from the historical, curricular, and strategic points of view. Finally, in the last section of the theoretical part, the possible ways of using digital technology in English lessons are described in more detail. The empirical part of this thesis describes research conducted with three secondary school teachers. This research works with data collected with the use of group interview and subsequent observations. The research observes subjective attitudes towards digital technologies in English lessons and the level of digital competence of designated teachers.
Digitální kompetence učitelů anglického jazyka
Keywords: učitel anglického jazyka; kompetence učitele; digitální kompetence; technologie ve výuce anglického jazyka; English teacher; teacher competences; digital competence; ICT in English teaching